Cultura, política, y ecología política del agua: una presentación - Damonte Valencia, Gerardo (2016)
This article introduces the special volume of the journal Anthropologica dedicated to the culture, politics, and political ecology of water. For this, fundamental concepts, such as hydrosocial territory and scarcity, as well as institutional processes, such as the implementation of governance models of water resources, necessary to analyze and understand the social phenomena associated with water are reviewed. This review integrates the presentations of the articles that make up the special volume.